Design and fabricate an acoustic emission sensor adapter for engine performance monitoring - Mohd Alhafiz, Maznan (2009)
This project was carried out to design and fabricate an Acoustic Emission (AE) sensor adapter for engine performance monitoring. Before fabrication process, a standard test that called Pencil Break Test must be conducted to check the suitability of the materials. Aluminium and Mild Steel were used as the material of the adapter. The source of the AE signals came from the breaking of the pencil leads (2H). The selection of the type of the pencil lead is based on the ASTM D-3363 hardness rating. The source of the AE signal was recorded by AE sensor with the help of the AED ver2.13 software. RMS amplitude was chose as the parameter for experiment. The three experiments were conducted which is without using adapter, using aluminium adapter and using mild steel adapter. The data from each experiment were analyzed statistically by Microsoft Excel and normal distribution graph was plotted. The graphs were compared and shows that the different between the three experiments. Based on the result, Mild Steel adapter give best result compare to Aliminium adapter.